2019
DOI: 10.2478/jomb-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide, lipid peroxidation products, and antioxidants in primary fibromyalgia and correlation with disease severity

Abstract: Summary Background Fibromyalgia syndrome (FMS) is characterized by altered pain perception with chronic, widespread musculoskeletal pain. The relationship between nitric oxide, oxidative stress and the severity of FMS has not been studied. This study evaluated NO levels in plasma, LPO products and antioxidants in Red Cell lysate in patients of FMS and correlated it with disease severity. Methods 105 FMS patients who fulfilled 1990 ACR Criteria and 105 age- and sex-matched healthy controls were recruited over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…This enzyme is not secreted by the salivary glands so its concentration in saliva reflects its concentration in blood [ 19 ]. Previous studies showed a lower catalase activity in blood in people with fibromyalgia than in healthy people [ 47 , 48 , 49 ]. This could indicate that people with FM have more susceptibility to the deleterious effects of ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme is not secreted by the salivary glands so its concentration in saliva reflects its concentration in blood [ 19 ]. Previous studies showed a lower catalase activity in blood in people with fibromyalgia than in healthy people [ 47 , 48 , 49 ]. This could indicate that people with FM have more susceptibility to the deleterious effects of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced concentration in thiol-rich compounds (including glutathione) was described in fibromyalgia blood samples [ 47 , 49 ]. Additionally, in red blood cells from people with fibromyalgia, a lower GPx activity was found [ 48 ]. These results also underline the lower antioxidative capacity of people with fibromyalgia [ 17 , 47 , 48 , 49 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that NO might play a dual role in cancer progression, depending on its concentration, and can act as a protumor or antitumor factor 57. Therefore, elevated NO levels in patients with leukemia can lead to a variety of chemical reactions in the biological system, including the induction of lipid peroxidation, inhibition of mitochondrial electron transfer, disruption of the antioxidant system, and ultimately exacerbation of the disease 58…”
Section: Discussionmentioning
confidence: 99%
“…To date, efforts in this direction have shown that oxidative stress may play a number of roles in the pathogenesis and severity of this disease. Shukla et al[ 37 ] reported a strong positive relationship between the FIQ scores and oxidative stress, which was exhibited by nitric oxide and lipid peroxidation. In the same study, a strong negative correlation between the FIQ scores and antioxidant enzymes was observed.…”
Section: Discussionmentioning
confidence: 99%